Urban green is more than the absence of city: Structural and functional neural basis of urbanicity and green space in the neighbourhood of older adults - Simone Kühn; Sandra Düzel; Anna Mascherek; Peter Eibich; Christian Krekel; Jens Kolbe; Jan Goebel; Jürgen Gallinat; Gert G. Wagner; Ulman Lindenberger (Landscape and Urban Planning, 2021)
The relationship between urbanization, the brain, and human mental health is subject to intensive debate in the current scientific literature. Particularly, since mood and anxiety disorders as well as schizophrenia are known to be more frequent in urban compared to rural regions. Here, we investigated the association between cerebral signatures, mental health and land use indicators (Urban Fabric and Urban Green) within a 1~km radius around the home address of 207 well-characterized older adults. We observed a negative association between Urban Fabric coverage and a positive association between Urban Green coverage and grey matter volume in perigenual/subgenual anterior cingulate cortex (p/sACC). Although p/sACC has repeatedly been associated with depressive symptoms, neither brain structure nor land use categories were related to measures of mental health. However, resting-state measure in p/sACC showed a negative association with Urban Fabric in our healthy sample, reminiscent of previous reports on major depression where p/sACC is often found to be reduced in activation. Interestingly, hierarchical regression analyses showed that Urban Green accounted for additional variance in brain structure beyond Urban Fabric. We take this finding as an exploratory result that hints at potentially salutogenic elements of green spaces (e.g. terpenes, nature sounds) that go beyond the absence of the detrimental elements of urban contexts (e.g. traffic noise, air pollution), which may inform the future search of environmental factors affecting mental health and disease.
Keywords: 330; Urban fabric; Urbanicity; Urban green; Brain structure; MRI